2002
DOI: 10.1046/j.1365-2842.2002.00864.x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of check‐bite registration and centric condylar position

Abstract: In a dentate subject a jaw relation can either be determined in maximum intercuspation and is as such given by the occlusal morphology, or the mandibular position can be allocated according to the centric position of the condyles. For comprehensive restorative treatment or analytic measures of the occlusion it is important to record the centric condylar position. Various registration methods have been described in the literature, but there is no consensus on which is the 'best'. The aim of the present study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1
9

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 19 publications
1
23
1
9
Order By: Relevance
“…The subjects were from 26 to 36 years of age and met the following inclusion criteria: [1] not undergoing orthodontic treatment [2]; absence of temporomandibular joint signs and symptoms [3]; a complete dentition excluding the third molars; and [4] in good health. The rights of all subjects were protected and the study was approved by the Colorado Multiple Institution Review Board.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The subjects were from 26 to 36 years of age and met the following inclusion criteria: [1] not undergoing orthodontic treatment [2]; absence of temporomandibular joint signs and symptoms [3]; a complete dentition excluding the third molars; and [4] in good health. The rights of all subjects were protected and the study was approved by the Colorado Multiple Institution Review Board.…”
Section: Methodsmentioning
confidence: 99%
“…At present, there is no established "gold standard" method of recording patients' centric relation (CR) position [1][2][3]. Rather, many different techniques are surrounded by open-ended controversy regarding their comparative reproducibility and/ or accuracy or even the necessity of mounting study casts in CR [4].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the dominant influence upon reproducibility was clinical technique rather than recording medium or the particular mandibular position recorded. Conversely, Utz et al 60 has suggested that reproducibility is unachievable, regardless of technique or technical excellence. Utz et al 60 may be right in that absolute reproducibility of RCP is impossible, however differences of 0.08 mm have lead Posselt 15 to conclude that these variations are 'probably clinically insignificant'.…”
Section: Comparison Of Rcp Guidance Methods Clinical Variation In Rcpmentioning
confidence: 99%
“…Znaczenie mają między innymi umiejętności operatora, zastosowana metoda, czas rejestracji, stan nerwowo-mięśniowy pacjenta oraz zastosowanie odpowiednich materiałów do rejestracji zwarcia. 54,55 Optymalny materiał do rejestracji położenia żuchwy względem szczęki powinien wykazywać niską lepkość początko-wą, a po związaniu być sztywny i stabilny objętościowo. [56][57][58] Jest wiele materiałów, które mogą być stosowane do rejestracji położenia żuchwy w relacji centralnej, jednak wszystkie one posiadają wady i zalety.…”
Section: Rejestracja Relacji Centralnejunclassified